Spectral analysis of the fur of different colour phases of Sciurus vulgaris: evidence for adaptive colouration - Zizda, Yu. (Theriologia Ukrainica, 2019)
The red squirrel (Sciurus vulgaris L.) is one of the most variable mammals by its coat colouration, which allows to distinguish up to 40 subspecies. The distribution of four different subspecies in the region of the Eastern Carpathians, including Poland and Ukraine, based on coat colouration is described in literature sources. The accordance of colour phases to subspecies can be determined only if to place them in a row of individuals having similar colouration. Thus, in this paper, we present the results of research on two forms of the red squirrel having different coat colouration typical for Ukraine (light, or orange-red and dark, or black-brown). The aim of the study was to describe the colour phases of the red squirrel by means of spectral analysis and digital ratios of the fur pigmentation (melanin). In order to achieve this goal, we measured the dependence of the light diffuse reflection on fur samples established with the help of standard chemical methods (using alkali, NaOH in different concentration levels). To conduct the research, fur samples of dark specimens (black, dark brown squirrels) were taken from the Zoological Museum of Uzhhorod National University, while specimens of the light phase (red, orange squirrels) were taken from the Zoological Museum of Ivan Franko Lviv National University. In total, 30 individuals were investigated. According to the rules of light reflection and its differentiation into colours, we expected to obtain distribution curves in the range from 400 to 560-800 nm. In the light forms, the diffusion reflection curve was expected to rise at 560 nm and at 610 nm in the red. With the darkening of the fur, the increase in diffusion reflection should have approached the infrared region of 800 nm. However, according to the obtained results, the reflection spectra for the dark individuals showed much less deviation of the curve’s right side than the spectra for most of the red individuals. However, orange samples with the similar deviations of the spectra right side were also observed among the black samples. There was no clear distribution among different colour phases of the squirrel regarding fur colouration intensity. At the same time, it is obvious that different pigments influence the darkness of the squirrel’s coat patterns. This fact may indicate the adaptive nature of colour in different colour phases.